Instrument for evaluation of sedentary lifestyle in patients with high blood pressure - Marcos Venícios de Oliveira Lopes; Viviane Martins da Silva; Thelma Leite de Araujo; Nirla Gomes Guedes; Larissa Castelo Guedes Martins; Iane Ximenes Teixeira (Associação Brasileira de Enfermagem, 2015)
ABSTRACTObjective:this article describes the diagnostic accuracy of the International Physical Activity Questionnaire to identify the nursing diagnosis of sedentary lifestyle.Method:a diagnostic accuracy study was developed with 240 individuals with established high blood pressure. The analysis of diagnostic accuracy was based on measures of sensitivity, specifi city, predictive values, likelihood ratios, effi ciency, diagnostic odds ratio, Youden index, and area under the receiver-operating characteristic curve.Results:statistical differences between genders were observed for activities of moderate intensity and for total physical activity. Age was negatively correlated with activities of moderate intensity and total physical activity.Conclusion:the analysis of area under the receiver-operating characteristic curve for moderate intensity activities, walking, and total physical activity showed that the International Physical Activity Questionnaire present moderate capacity to correctly classify individuals with and without sedentary lifestyle.